Encuentro de Historiadores del Valle del Henares. 10° 2006 / Alcalá de Henares (946.027-11(063) Cuenca del Henares)
816 p. 24 cm. | Tít. del lomo : Actas del X Encuentro de Historiadores del Valle del Henares